SISTEM INFORMASI SANTRI DI PONDOK PESANTREN DARUL MUHTADIIN : Islamic Boarding School;System;Data Processing;Information. - Megawaty, Merti; Nilawati; Beri Saputra, Reza (FORTECH (Journal of Information Technology), 2021)
Darul Muhtadiin Islamic Boarding School is an Al-Qur'an and Yellow Book Education Park. The problems that exist today are the storage, processing, and delivery of information that occurs in this Darul Muhtadiin Islamic boarding school, which includes student data, ustadz data, student scores, and subject scheduling which often occurs because of data duplication because the data that has been processed is not organized properly. good. The purpose of this study is to identify user needs for input, process and output to produce an information system to support the Darul Muhtadiin Islamic boarding school. The research approach used in this research is observation, data collection, system analysis and design, application development and implementation. The analytical tool used is Data Flow Diagram (DFD). The programming language used is PHP and the database uses MySQL. This research produces a Web-Based Data Processing Information System, which is expected to be more time efficient, especially in processing students' grades and making it easier for parents or guardians of students to monitor the progress of their children's grades.